(untitled) (International Journal of Nursing Education, 2020)
There has been tremendous increase in interest in vitamin D in both health and disease in the last two decades. The chief reason for this is the discovery of vitamin D receptor (VDR) in virtually every tissue and thousands of VDR binding sites throughout the genetic machinery controlling multiple genes. This increased interest has been reflected in the request for estimation of serum level and prescription of supplements. In this changing scenario, nurses should be aware of both the basic science and clinical correlation of vitamin D. This article is a summary of the basic science with practical clinical applications relevant for nurses.